Overlaying Monolayer Metal–Organic Framework on PtSe2‐Based Gas Sensor for Tuning Selectivity. (12th September 2022) - Cho, Seong Rae; Kim, Dong‐Ha; Jeon, Mingyu; Rani, Pragya; Gyeon, Minseung; Kim, Yongman; Jo, Min‐kyung; Song, Seungwoo; Park, Jeong Young; Kim, Jihan; Kim, Il‐Doo; Kang, Kibum
Abstract: Transition metal dichalcogenides (TMDs) have attracted significant interest as gas‐sensing materials due to their unique crystal structure and surface. However, there are still issues when it comes to expanding the types of sensing gases for the TMD gas sensors. To extend gas‐sensing selectivity for the TMD gas sensors in this study, a monolayer (ML) 2D metal–organic framework (MOF) is introduced on top of the PtSe2 gas sensor, thereby tuning the major sensing analyte of PtSe2 from NO2 to H2 S. Density functional theory calculations elucidate that the metal species of ML MOFs are attributed to the tuned selectivity of the analytes, based on the difference in binding energies. It is also demonstrated that ML MOF maintained the high responsivity of the pristine PtSe2 even at a low concentration of gas (200 ppb). This is further confirmed through the molecular dynamics simulations, which reveal that the ML feature of the ML MOF is highly essential to preserve the intrinsic ultra‐low limit detection properties of pristine PtSe2 . Abstract : The monolayer 2D metal–organic framework is introduced to tune the gas‐sensing selectivity of PtSe2, one of the most promising gas‐sensing materials in transition metal dichalcogenides. The tuning mechanism is revealed by density functional theory calculations. The monolayer metal–organic framework also preserves ultra‐low detection limit of PtSe2, and it is elucidated by molecular dynamics simulation.